Penerapan Pendidikan Multikultural Berbasis Projek Penguatan Profil Pelajar Pancasila (P5) pada Peserta Didik Kelas VII di SMP Negeri 1 Bontang - Sukma Prastia Darma; Jamil Jamil; Jawatir Pardosi (International Forum of Researchers and Lecturers, 2024)
Understanding multicultural diversity means accept exists diversity expression containing culture values humanity and beauty For That so Already appropriately outlook multiculturalism grounded in the world of education. Multicultural education must taught and instilled since early. For avoid problems in Education like brawls and fights student, action crime committed student, action immorality, violence, bullying and other acts deviated other needed exists effort repair in the world of education so that there are problems the No protracted. One of business real thing that can be held that is with multicultural education, dangan method implementing multicultural education in every formal and non-formal educational activities at school. Study This aim For know role head school, teacher, and parent involvement participant educate in planning learning P5 activities at SMP Negeri 1 Bontang. And to know How application multicultural through project P5 theme Global diversity in class VII of SMP Negeri 1 Bontang. Then fo know evaluation from implementation of multicultural education in project P5 theme Global diversity in class VII of SMP Negeri 1 Bontang. Research methods This is qualitative. Result of study This state that implementation of learning strategies multicultural through P5 project at SMP Negeri 1 Bontang has succeed create environment inclusive, supportive learning development understanding culture, and strengthen Skills social student.